Violence and harassment against healthcare workers: a psychological-clinical perspective on a survey in a Policlinic Hospital - Vitale, Ermanno; Vella, Francesca; Matera, Serena; Mazzeo, Silvia; Farrauto, Chiara; Filetti, Veronica; Rapisarda, Venerando; Farruggio, Giorgia; Vitale, Noemi Maria; Uccelli, Eleonora; Fakhrou, Abdulnaser; Rapisarda, Lucia; et al. (Frontiers in Public Health, 2025)
ObjectiveThe aim of this study was to assess the prevalence and psychological impact of workplace violence (WPV) among healthcare workers (HCWs) in a large university hospital in Southern Italy, and to identify occupational and demographic risk factors.MethodsA cross-sectional observational study was conducted from January to December 2023. A total of 997 HCWs voluntarily completed a validated, anonymous questionnaire based on the “Workplace Violence in the Health Sector” (WVHS) tool. The instrument assessed exposure to different types of WPV (physical, verbal, bullying, sexual and racial harassment) and its emotional and occupational consequences. Statistical analyses included descriptive statistics, linear regression and ANOVA (p < 0.05).Results27% of HCWs reported experiencing at least one form of WPV in the past 12 months. Verbal violence was the most common (85%), followed by bullying (26%). Nurses, resident doctors, younger workers, and those working night shifts were more frequently affected. Victims showed higher use of psychotropic drugs and psychotherapy (p < 0.001).ConclusionWPV is highly prevalent and underreported in healthcare settings, with significant mental health repercussions. The findings highlight the need for preventive strategies, institutional support, and the key role of occupational physicians in early identification and intervention.